(untitled) (CIPEEX, 2025)
Anxiety has become increasingly common, affecting work, leisure, rest, and quality of life. Although there are several drug treatments available, prolonged use can lead to dependence, significant side effects, and, in some cases, serious consequences such as hallucinations and prostration. In this circumstance, aromatherapy, more specifically with essential oils, is a valuable aid, as scientific studies and research demonstrate its positive effect on anxiety control and make it a complementary practice for treatment. The present study aimed to evaluate anxiety control through the use of essential oils and, consequently, the improvement in quality of life. A descriptive literature review was conducted in the PubMed and Scielo databases, with a time frame of 5 years (2020 to 2025). After analyzing the articles, it was identified that essential oils of Lavandula angustifolia (lavender), Citrus bergamia (bergamot), Citrus aurantium (bitter orange), Citrus sinensis (sweet orange), Pelargonium graveolens (rose geranium), and Protium heptaphyllum (banyan tree) have a significant effect against anxiety, acting on GABA receptors and, consequently, promoting relaxation, a more favorable mood, and a reduction in symptoms caused by excessive stress. Clinical studies have shown positive effects in children, reducing anxiety in moments of high stress with the use of lavender and orange, but in people with autism spectrum disorder, the results were not significant. In adults and the elderly, the use of essential oils was of great value, reducing generalized anxiety and providing an improvement in the quality of life of people suffering from fibromyalgia. The use of Protium heptaphyllum provided better quality of life, mood, and sleep, but had no impact on fibromyalgia pain. Data analysis showed that more than 80% of the studies analyzed had significant effects with low side effects, promoting a complementary practice for the treatment of anxiety. It is concluded that the use of essential oils provides a complement to the treatment of anxiety without major risks, accessible and effective. Despite this, controlled clinical trials are still necessary to standardize doses, methods of administration, and duration of use.